Needs of frail elderly people in informal settlements - P du Rand; K Engelbrecht (AOSIS, 2001)
The frail elderly in informal settlements find themselves in an extremely vulnerable position due to a number of factors, namely, their increasing dependency status, limited resources and adverse physical environment. Various aspects that influence the aged in their present environment will be highlighted. A survey method was used to explore and to describe the world in which they live in informal areas. The attitude, expectation and needs of the elderly in respect of their care was also determined. A random cluster sample was taken. Data was collected by means of interviews in terms of a semi-structured questionnaire. It appears that the frail elderly were happy in the environment in which they received care in spite of their unfavourable physical environment and limited resources. The communities where the frail elderly lived were largely unaware of the valuable inputs they can make regarding the care of the aged. This necessitates the development of programs in the heart of communities, owned by communities, where all role players in the care of the aged participate.